El dibujo infantil como estrategia metodológica para el desarrollo de la creatividad en los niños de la Unidad Educativa Canadá en el período 2019 - 2020 - Gutama Paredes, Ricardo Javier (2020)
This research takes to establish children's drawing as a tool to develop creativity in fifth year children in the Basic Education Unit of Education Canada. This research has been carried out when we realized that the classes given by the teachers of this institution were very traditionalist, so the classes became monotonous, boring and the students' distraction at the moment of learning. The development of this work has allowed us to know the abilities of each student, this is reflected in the way they develop when drawing and expressing their creativity. The objective of this research is to promote children's drawing as a methodological strategy for the development of creativity in children in the fifth year of Basic Education. This work is based on different types of research such as: exploratory, descriptive and explanatory research, in the same way this research is focused on the qualitative approach and on the non-experimental design, the methods that were put into practice in this research are; inductive method and descriptive method, the technique used was observation and the instrument that was applied in this research is the observation guide. When the research problem was detected, it was established as a proposal to develop children's drawing by applying the microdrawing technique to strengthen creativity in the teaching-learning process. By putting this proposal into practice we have obtained very good results in the fifth year students, since when applying the micro-drawing technique the students are very motivated and enthusiastic about learning, this technique not only develops creativity, but we could also realize that it promotes the development of the socioaffective part and the imagination of the student.